PEMANFAATAN TUMBUHAN BAMBU OLEH MASYARAKAT DI KECAMATAN OBA UTARA KOTA TIDORE KEPULAUAN - Dewi Fitria Muhtar; Yumima Sinyo; Hasna Ahmad (Universitas Khairun, 2017)
Bamboo is a plant that is very beneficial for the economic life of society. Until now, bamboo has been used very widely, ranging from the use of the most simple technologically into use high technology on an industrial scale. Traditionally, generally bamboo used for various purposes such as household appliances, handicrafts and foodstuffs. The objectives of this study was to determine the plant species of bamboo and its utilization by the community in the District of North Oba. The method used in this study is the direct survey Method in the field. The technique of analysis data conducted by using descriptive Explorative analysis with describing the type of bamboo plant. The results of this study can found that 10 species of 4 genera: Schizostachyum lima (bambu tui), Schizostachyum brachyladumi (bambu Jawa), Bambusa atra (bambu loleba), Bambusa vulgaris_vittata (bambu kuning), Dendrocalamus strictus (bambu batu), Bambbusa glaucophylla (bambu putih), Bambusa vulgaris (bambu Ampel), Bambusa blumeana (thorns bamboo), Bambusa balcooa (bambu balku), Gigantochloa Apus Kurz (Rope Bamboo). And its use is the manufacture chairs by craftsmen, fencing, windows, home construction, making vegetables from its rizom (the shoots of bamboo), and as an ornamental plant in the yard.Key Words: Utilization, Bamboo Plant, North Oba, Tidore Kepulauan